UiTM and University of Toyama's international online exchange project: a journey of knowledge and collaboration - UiTM, UiTM Global (Office of International Affairs (OIA), 2024)
The International Online Exchange Project was launched in March T2021 and is still ongoing. It is a remarkable initiative aimed at enhancing students' knowledge and expertise in Sustainable Development and Data Science. This project brought together young minds from primary and middle schools in Malaysia and Toyama. Japan, under the auspices of the Faculty of Education, University of Toyama. This collaboration between elementary schools in Malaysia and Toyama has grown into a vital educational exchange ,supported by the Faculty of Education, University of Toyama, and the College of Engineering. UiTM Shah Alam. The primary objective is to elevate students' understanding of sustainable practices and data science applications in their respective educational contexts.